ETHICS OF GOVERNMENT APPARATUSES IN IMPROVING PUBLIC SERVICES AT THE PEGADEN DISTRICT OFFICE, SUBANG REGENCY - Margaretha Retno Daru Dewi (SEAN Institute, 2023)
In the study of public administration, ethical arrangements for civil service administration, also known as the code of ethics for civil servants, are provisions or standards regulating the moral conduct of civil servants. The ethics of the state civil apparatus include moral teachings and principles of good behavior for officials/civil servants in carrying out their responsibilities and providing community services. This study seeks to examine the ethical responsibilities of public servants at the Pegaden District Office in Subang Province. To meet community needs and establish trust in local government, it is necessary to provide high-quality, ethical public services. This qualitative research method collects information through interviews, observations, and documentation studies. The results showed that several public service problems which were the source of apparatus problems were difficult to access where the service implementing unit was, not yet informative, did not listen to the aspirations of the community, was not responsive, lacked coordination, was inefficient and had a long bureaucracy. In an effort to overcome this, the Pegaden sub-district government of Subang Regency took steps which included establishing service standards, developing standard operating procedures (SOP), conducting customer satisfaction surveys and developing a complaint management system.